Understanding religious conversion - Rambo, Lewis R. (Lewis Ray), 1943- (Yale University, 1993)
Looking at a wide variety of religions, this work offers an exploration of religious conversion. The phenomena is approached from a variety of disciplines, including psychology, sociology, theology and anthropology.
Keywords: Conversion.; Psychology and religion.; Religion and Psychology; Psychologie et religion.; RELIGION -- Spirituality.; RELIGION -- General.; Psychology and religion; Conversion; Konversion -- Religion; Bekering.; Conversão religiosa.; Religião.; Christianity -- Religious experiences -- Conversion